Transformational Role of Computers in Education Management: Optimizing Learning Efficiency and Effectiveness - Rosmiati Rosmiati; Akhmad Syahid; Idawati Idawati; Salim Hasan; Nur Setiawati; Muh. Azhar Burhanuddin (International Journal of Artificial Intelligence Research, 2022)
This discussion addresses the role of teachers in the use of tablet computers in the context of eLearning, the advantages, and challenges of using eLearning, student learning outcomes, the influence of locus of control, the theory of planned behavior, and its managerial and theoretical implications. The use of tablet computers in learning provides new opportunities for teachers to engage students interactively and deeply. The advantages of using eLearning include better accessibility to learning resources and expansion of learning beyond the classroom. However, challenges such as unequal accessibility of technology require the role of teachers in ensuring equitable access for all students. The teacher's role in the use of tablet computers is a major determinant in student learning outcomes. Teachers must be able to observe and evaluate students' learning progress and use learning outcome data to improve learning. The influence of locus of control and the theory of planned behavior also plays a role in the use of tablet computers. Teachers can help students develop an internal locus of control and apply the principles of the theory of planned behavior to increase students' motivation and independence in learning. Managerial implications include the importance of training and development for teachers, development of educational policies that support the use of technology, and collaboration between educational institutions and stakeholders. Theoretical implications include the development of technology-based learning theory, motivation theory in the context of technology, and the application of planned behavior theory in the use of technology. The discussion provides a better understanding of the importance of the role of teachers, the use of tablet computers, innovative learning strategies, policy development, improving educational accessibility, and developing educational theories in the context of technology. Its managerial and theoretical implications provide guidance for educational managers and researchers to improve the quality of education and utilize technology effectively in the learning process.